Mesoscale Ordering and Charge-Transport of Crystalline Spiro-OMeTAD Organic Semiconductors - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2017)
The mesoscale ordering and charge-transport of crystalline spito-OMeTAD, :a hole-transporting material extensively used in perosvkite and dye-sensitized solar cell applications, were explored-Using:, molecular dynamics and hole mobility calculations. Morphologies were evaluated through conformational changes, nematic; Order, and paracrystallinity at various temperatures. Charge transport is predicted with electronic structure methods employing a hopping mechanism. Our calculations show that along with strong fluorene backbone packing, phenylenes in the metlicrtyphenyl amine substituents of spiro-OMeTAD are an integral part of the material performance. Backbone and substituent paracrystallinitypredictions, showed highly ordered crystalline phase. The methoxyphenyl substituents have multiple confOrinations in the unit-cell scale, but interphenylene electronic-coupling remain nearly constant. A thermal increase in positional disorder results in a systematic increase in energetic disorder and a decrease in hole mobility. The predicted crystalline hole mobility is approximately two-orders of magnitude higher than the experimental thin-film measurements, Indicating that the perforrnance of spiro-OMeTADs can be improved significantly by exploiting crystallinity.
Keywords: PEROVSKITE SOLAR-CELLS; HOLE-TRANSPORT; REORGANIZATION ENERGY; CARRIER MOBILITY; ATOMIC CHARGES; STATE; TRANSITION; DEPOSITION; EFFICIENCY; DYNAMICS